HUBUNGAN RETURN SAHAM DAN INFLASI DI INDONESIA - Triaryati, Nyoman (Jurnal Keuangan dan Perbankan, 2014)
The effect of inflation to the stock return research had been held since three decades ago based on GeneralizeFishers Hypotheses, but how inflation influenced stock return had become a debate until today. In Indonesiamost of the related research used inflation as one of the variables that influenced stock return despite of others inshort period of time. This research investigated the effect of inflation to the stock return in Indonesia within fifteenyears, which was divided into 3 (three) periods of time reflecting different economic growth for each of it. Thepurpose of this allotment was to see the consistency how inflation influenced the stock market. Using a secondarydata from monthly inflation and IHSG period 1998 until 2012, included three hundred and sixty observation,simple regression model analyses was applied. This research acknowledged that inflation negatively influencedstock return in a long time period, but it did not exist in the short time period, except when the level of inflationreached 10%. In conclusion, inflation influence on the stock return was not ascertained by how long the investigationwas held but if there was any inflation rate reaching 10% within the period of investigation.